Oblique Analog Models (diségno, 2024)
Every architectural drawing is by its nature the result of a combined operation of projection lines and intersection with a plane, which is usually a sheet of paper. Even a sketch, in its rarefied figuration, evokes such operations for a representation of a design idea or an executive work, in an unequivocal icasticity. [read more]